Extended Lie algebraic stability analysis for switched systems with continuous-time and discrete-time subsystems - Zhai, Guisheng; Xu, Xuping; Lin, Hai; Lui, Derong (Zielona Góra: Uniwersytet Zielonogórski)
We analyze stability for switched systems which are composed of both continuous-time and discrete-time subsystems. By considering a Lie algebra generated by all subsystem matrices, we show that if all subsystems are Hurwitz/Schur stable and this Lie algebra is solvable, then there is a common quadratic Lyapunov function for all subsystems and thus the switched system is exponentially stable under arbitrary switching.
Keywords: switched systems; common quadratic Lyapunov functions; Lie algebra; exponential stability; arbitrary switching; dwell time scheme